Rational Autologous Cell Sources For Therapy of Heart Failure – Vehicles and Targets For Gene and RNA Therapies - Lampinen, Milla; Vento, Antti; Laurikka, Jari; Nystedt, Johanna; Mervaala, Eero; Harjula, Ari; Kankuri, Esko (Current Gene Therapy, 2016)
This review focuses on the possibilities for intraoperative processing and isolation of autologous cells, particularly atrial appendage-derived cells (AADCs) and cellular micrografts, and their straightforward use in cell transplantation for heart failure therapy. We review the potential of autologous tissues to serve as sources for cell therapy and consider especially those tissues that are used in surgery but from which the excess is currently discarded as surgical waste. We compare the inculture expanded cells to the freshly isolated ones in terms of evidence-based cost-efficacy and their usability as gene- and RNA therapy vehicles. We also review how financial and authority-based decisions and restrictions sculpt the landscape for patients to participate in academic-based trials. Finally, we provide an insight example into AADCs isolation and processing for epicardial therapy during coronary artery bypass surgery.
Keywords: Gene therapy